The conceptual, structural and organisational features of the doctoral programme in information and communication sciences at the University of Zagreb - Lazić, Nikolaj; Lasić Lazić, Jadranka; Špiranec, Sonja (Qualitative and Quantitative Methods in Libraries; Vol 8 No 3 (2019): September 2019 Issue, 2019)
Purpose: The aim of this paper is to present the conceptual and structural features of the doctoral programme in the field of information and communication sciences at the University of Zagreb. Since an analysis of a doctoral study programme is inseparable from deliberations over the identity and recognisability, and hence the status, of a given scientific field, the paper will attempt to provide an answer to questions of theoretical groundwork and dilemmas that shaped the conceptual framework of the University’s present, reformed doctoral programme in information and communication sciences, and present how its organisation has been defined by EU strategies and policies in science. Methodology/approach: Addressing a lack of relevant resources that would enable the gaining of systematic insight into the history and development of doctoral programmes in information and communication sciences in Croatia, the paper presents the results of the qualitative analysis focusing on literature outlining the theoretical profile of the field of information and communication sciences as well as on EU guidelines on PhD programmes to present problems and solutions related to the restructuring of doctoral programmes in this field. Findings: The paper provides a systematic overview of the conceptual and structural features of the doctoral programme in information and communication sciences at the University of Zagreb and presents arguments according to which all attempts at its reform are inseparable from deliberations over the field’s theoretical scope, its recognisability and the related status. Also, it indicates as necessary that this doctoral programme has to be (re)structured in such a way as to respond to the theoretical and intellectual dispersion characterising the field and its modules be based on EU guidelines on doctoral study programmes. Originality/value: The paper presents a valuable response to a relative lack of resources and literature on the (re)modelling of doctoral programmes in the field of information sciences based on the analysis of theoretical dilemmas present in the field and EU guidelines on structuring doctoral programmes.